Cost-effectiveness analysis of mindfulness-based cognitive therapy in patients with anxiety disorders in secondary mental health care settings alongside a randomized controlled trial - Sado, Mitsuhiro; Koreki, Akihiro; Ninomiya, Akira; Kurata, Chika; Park, Sunre; Fujisawa, Daisuke; Kosugi, Teppei; Nagaoka, Maki; Nakagawa, Atsuo; Mimura, Masaru (Frontiers in Psychiatry, 2024)
Introduction Anxiety disorder is one of the most prevalent mental disorders. Mindfulness-based cognitive therapy (MBCT) is effective for treating anxiety disorders. However, no studies have investigated the cost-effectiveness of MBCT for anxiety disorders. We aimed to conduct a cost-effectiveness analysis alongside a randomized controlled trial (RCT) to clarify the cost-effectiveness of MBCT for anxiety disorders. Methods A cost-effectiveness analysis alongside an RCT was conducted for 8 weeks in 40 patients with anxiety disorders at a university hospital. Patients (1) aged 20–75 years; (2) who were diagnosed with panic disorder/agoraphobia or social anxiety disorder based on the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria; and (3) who provided written consent were analyzed. The participants were allocated randomly (1:1 ratio) to the augmented MBCT group (i.e., MBCT plus treatment as usual [TAU]) or TAU (waitlist control) group. The cost-effectiveness was assessed using the incremental cost-effectiveness ratio (ICER), which is the ratio of the incremental costs divided by the incremental state-trait anxiety inventory- state (STAI-S), state-trait anxiety inventory- trait (STAI-T), and quality-adjusted life years (QALYs). The QALYs were estimated using The Japanese version of EuroQoL five-dimensional 3-level questionnaire. The unit cost data were derived from the government-regulated fees. This study was conducted from a public healthcare insurance perspective. No discount rates were considered. Results A total of 38 participants with complete data were included in the analysis. The MBCT was JPY 13,885 more than the cost of TAU and was associated with a STAI-S, STAI-T, and QALY increase of 10.13, 12.00, 0.009 respectively. The ICER were JPY 1,371 (USD13) per STAI-S, JPY 1,157 (USD 11) per STAI-T, and JPY 1,566,357 (USD 14,940) per QALY respectively. MBCT had an 77.5% probability of being cost-effective at a willingness to pay threshold in Japan (JPY 5,000,000 per QALY). The results of the four one-way sensitivity analyses supported the robustness of the base-case analysis findings. Discussion Augmented MBCT for anxiety disorders is cost-effective compared with TAU post-treatment from a public healthcare insurance perspective. Future studies should include long-term observations, and analysis from a societal perspective.